Reflection-AI: artificial intelligence as a redefining force for expressive filmmaking in film schools - Monserrat, Ana Laura; Srnec, Nahuel Matias (Frontiers in Communication, 2025)
Artificial Intelligence (AI) is reshaping film education, prompting critical reflection on its role in creative learning and artistic innovation. This study investigates AI’s potential to contribute to a new wave of expressive cinema by examining how students engage with AI tools in educational settings. Combining a classroom-based experiment with three surveys across different learning contexts, we analyze students’ creative responses and ethical concerns. Results reveal a consistent ambivalence: while text-based AI tools were perceived as helpful, visual AI outputs were often described as inauthentic, overly polished, or hegemonic. Notably, many students who voiced concerns about AI’s impact on creativity also acknowledged its potential to enhance artistic work. These contradictions point to an ongoing negotiation between enthusiasm and resistance. Drawing on this data, we discuss the pedagogical implications of integrating AI into filmmaking education and propose a framework that distinguishes between technical and artistic processes. We argue that AI can support cinematic expressiveness if integrated critically, preserving space for experimentation, failure, and personal voice. Ultimately, the classroom emerges as a key site for shaping how AI will influence the future of avant-garde cinema.